Ageing Organizations: Reviewing the Literature and Making a Few Recommendations for Human Resource Management - Salomao Filho, Alfredo; Tillmanns, Tanja; Corrigan, Trudy (Merits, 2023)
In an ageing society, organizations must consider the inclusion and effective management of older professionals if they wish to remain competitive. Besides having harmful and far-reaching effects on people’s health, age discrimination in the workplace leads to absenteeism, lower levels of productivity, and early retirement. Within such a context, this problematic organizational feature of most Western, now ageing, organizations and labour markets starts gaining more relevance. However, to date there has been little discussion, research, or policy development to ensure that older employees’ skills and capabilities are optimally put to use by organizations without the occurrence of ageism. We present the results of a systematic literature review based on 30 studies in the context of ageing organizations to make recommendations for human resource management. We suggest an approach to effectively manage intergenerational organizations, reducing the occurrence of age discrimination and its related consequences, as well as to achieve high employee engagement. Our review indicates that a strong ethics framework that is continuously followed, disseminated, and updated by management, together with a combination of efforts from all stakeholders, may accomplish the best results towards a culture that respects and values people of all ages at work, positively impacting on productivit
Keywords: human resources management; ageing organizations; older employees; organizational policy; recruitment and training; intergenerational; ageism